PENGARUH PRAKTIK CORPORATE GOVERNANCE DAN KARAKTERISTIK PERUSAHAAN TERHADAP AUDIT REPORT LAG - Kuslihaniati, Desi Fia; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this research is to test the influence of corporate governance practice and the characteristics of the companies to the audit report lag on companies which are listed in Indonesia Stock Exchange in 2010-2014 periods. The samples have been selected by using stratified random sampling and 320 annual financial statements have been obtained from the official sites Indonesia Stock Exchange (www.idx.co.id). The test has been done by using multiple linear regressions analysis and SPSS 20 version instrument and the independent variables i.e.: independent board of commissioners, meeting of board of commissioner, independent board of directors, meeting of board of directors, meeting of audit committee, firm size, profitability, firm type, and audit quality to the dependent variable i.e. audit report lag. The result of the research shows that 4 variables have an influence and 5 variables have not got any influence by audit report lag. Four variables which have negative and significant influence to the audit report lag are meeting of audit committee, firm size, profitability, and firm type. Five variables which do not have any influence to the audit report lag are independent commissioner, meeting of board of commissioner, independent board of directors, meeting of board of directors, and audit quality.Keywords: Corporate Governance, Characteristic of the Company, Audit Report Lag.